Performance of the Plusoptix A09 Photoscreener in Detecting Amblyopia Risk Factors in Chinese Children Attending an Eye Clinic - Yan, Xiao-Ran (PLoS One, 2015)
PURPOSE: To assess the accuracy of the Plusoptix A09 photoscreener in detecting amblyopia risk factors in children and determine referral criteria when using Plusoptix A09 for a large-scale vision screening. METHODS: Pediatric patients attending our eye clinic underwent a comprehensive ophthalmic examination that included photorefraction, orthoptic examination, anterior segment assessment, fundus examination and cycloplegic retinoscopy. The measurements were collected for statistical analyses. RESULTS: One hundred and seventy-eight children (mean age ± SD: 6.2±2.4 years, range: 2.2 to 14.1 years) were included in the study. The mean spherical equivalent (SE) obtained using Plusoptix A09 (P(SE)) was 0.57 D lower than that obtained from cycloplegic retinoscopy (CR(SE)) (P = 0.00). However, there was no statistically significant difference of Jackson cross cylinder J(0) and J(45) between Plusoptix A09 (P(J)) and cycloplegic retinoscopy (CR(J)) (P = 0.14, P = 0.26). The relationship of SE obtained from Plusoptix A09 and SE obtained from cycloplegic retinoscopy was presented as the equation: CR(SE) = 0.358 + 0.776 P(SE) + 0.064 P(SE) (2) + 0.011 P(SE) (3). Based on the Receiver Operating Characteristic (ROC) curve, the Plusoptix A09 had an overall sensitivity of 94.9% and specificity of 67.5% for detecting refractive amblyopia risk factors. The sensitivity and specificity of the Plusoptix A09 for detection of strabismus were 40.7% and 98.3%, respectively; detection of amblyopia and/or strabismus was 84.7% and 63.2%, respectively. CONCLUSIONS: The Plusoptix A09 photoscreener underestimated hyperopia and overestimated myopia according to SE when compared with cycloplegic retinoscopy. The accuracy of the Plusoptix A09 in detecting amblyopia risk factors in children could be improved by the regression equation and optimized criteria for refractive amblyopia risk factors developed in the present study. Moreover, the Plusoptix A09 photoscreener is not suitable for a large-scale strabismus screening when it is applied solely.